Electrochemical slurry composition and preparation method thereof

JP2025023033AInactive Publication Date: 2025-02-1424M TECHNOLOGIES INC
3 Cites 0 Cited by

Patent Information

Application Number
JP2024206362
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2013-03-15
Filing Date
2024-11-27
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure 2025023033000001_ABST
    Figure 2025023033000001_ABST
Patent Text Reader

Abstract

To provide a semisolid suspension, and in particular to a system and a method for preparing a semisolid suspension for use as an electrode in an electrochemical device such as a battery.SOLUTION: In some embodiments, a method of preparing a semisolid electrode includes combining a certain amount of active material with a certain amount of electrolyte to form an intermediate material. Next, in order to form an electrode material, the intermediate material is combined with a conductive additive. The electrode materials are mixed to form a suspension having a mixing index of at least about 0.80 and then formed into a semisolid electrode.SELECTED DRAWING: Figure 4A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application is a continuation of and claims priority to U.S. patent application Ser. No. 13 / 832,861, filed Mar. 15, 2013, entitled "Electrochemical Slurry Compositions and Methods for Preparing the Same," which claims priority to U.S. Provisional Patent Application No. 61 / 659,248, filed Jun. 13, 2012, U.S. Provisional Patent Application No. 61 / 659,736, filed Jun. 14, 2012, U.S. Provisional Patent Application No. 61 / 662,173, filed Jun. 20, 2012, and U.S. Provisional Patent Application No. 61 / 665,225, filed Jun. 27, 2012, all of which are incorporated herein by reference in their entireties.

[0002]

[0002] This application also claims priority to U.S. Provisional Patent Application No. 61 / 665,225, filed June 27, 2012, entitled "Electrochemical Slurry Compositions and Methods for Preparing the Same," the disclosure of which is incorporated herein by reference in its entirety.

[0003]

[0003] This application also claims priority to U.S. Provisional Patent Application No. 61 / 662,173, filed June 20, 2012, entitled "Electrochemical Slurry Compositions and Methods for Preparing the Same," the disclosure of which is incorporated herein by reference in its entirety.

[0004]

[0004] This application also claims priority to U.S. Provisional Patent Application No. 61 / 659,736, filed June 14, 2012, entitled "Electrochemical Slurry Compositions and Methods for Preparing the Same," the disclosure of which is incorporated herein by reference in its entirety.

[0005]

[0005] This application also claims priority to U.S. Provisional Patent Application No. 61 / 659,248, filed June 13, 2012, entitled "Electrochemical Slurry Compositions and Methods for Preparing the Same," the disclosure of which is incorporated herein by reference in its entirety.

[0006]

[0006] Embodiments described herein relate generally to semi-solid suspensions, and more particularly to systems and methods for preparing semi-solid suspensions for use as electrodes in electrochemical devices, such as batteries. [Background technology]

[0007]

[0007] Batteries are typically constructed of solid electrodes, separators, electrolytes, and ancillary components such as packaging for current carriers to terminals, thermal management, cell balancing, integration, and / or other such components. Electrodes typically contain active materials, conductors, binders, and other additives.

[0008]

[0008] Some known methods for preparing batteries include coating a metal substrate (e.g., a current collector) with active materials, conductive additives, and binders dissolved in a solvent, evaporating the solvent, and calendaring the dried solid substrate to a specific thickness. Then, electrodes are cut and packaged with other components, infiltrated with electrolyte, and the entire package is then sealed.

[0009]

[0009] Such known methods generally involve complex and expensive manufacturing steps such as casting the electrodes, and are only suitable for electrodes of limited thickness, e.g., less than 100 μm. These known methods of producing electrodes of limited thickness result in batteries with lower capacity, lower energy density, and higher ratio of inactive components to active materials. Furthermore, the binders used in known electrode formulations can increase the tortuosity of the electrode and reduce its ionic conductivity. Therefore, it is a constant goal of energy storage system development to simplify and reduce manufacturing costs, reduce inactive components of the electrodes and the finished battery, and improve performance. Summary of the Invention

[0010]

[0010] The embodiments described herein relate generally to semi-solid suspensions, and in particular to systems and methods for preparing semi-solid suspensions for use as electrodes in electrochemical devices, such as batteries. In some embodiments, a method for preparing a semi-solid electrode includes combining an amount of active material with an amount of electrolyte to form an intermediate material. The intermediate material is then combined with a conductive additive to form an electrode material. The electrode material is mixed to form a suspension having a mixing index of at least about 0.80, which is then formed into a semi-solid electrode. [Brief description of the drawings]

[0011] [Figure 1] 1 is a plot showing the effect of mixing method on the conductivity of a semi-solid electrode for a range of compositions, according to various embodiments. [Diagram 2]

[0012] 1 is a plot showing the effect of mixing method on the yield stress of a semi-solid electrode for a range of compositions, according to various embodiments. [Figure 3A]

[0013] FIG. 1 is a schematic diagram of a semi-solid suspension according to various embodiments. [Figure 3B] 1 is a schematic diagram of a semi-solid suspension according to various embodiments. [Figure 3C]1 is a schematic diagram of a semi-solid suspension according to various embodiments. [Figure 4A] 1 is a schematic diagram of a semi-solid suspension according to various embodiments. [Figure 4B] 1 is a schematic diagram of a semi-solid suspension according to various embodiments. [Figure 4C] 1 is a schematic diagram of a semi-solid suspension according to various embodiments. [Diagram 5]

[0014] 1 is a plot of conductivity versus conductive additive loading for semi-solid electrodes according to various embodiments. [Figure 6A]

[0015] 1 illustrates electrode slurry mixtures having different conductive additive loadings according to various embodiments. [Figure 6B] 1 illustrates electrode slurry mixtures having different conductive additive loadings according to various embodiments. [Figure 6C] 1 illustrates electrode slurry mixtures having different conductive additive loadings according to various embodiments. [Figure 7]

[0016] 1 is a plot illustrating the rheological properties of a slurry formulation according to various embodiments. [Figure 8] 1 is a plot illustrating the rheological properties of a slurry formulation according to various embodiments. [Figure 9] 1 is a plot illustrating the rheological properties of a slurry formulation according to various embodiments. [Figure 10] 1 is a plot illustrating the rheological properties of a slurry formulation according to various embodiments. [Figure 11]

[0017] 1 is a plot illustrating mixing curves according to various embodiments. [Figure 12] 1 is a plot illustrating mixing curves according to various embodiments. [Figure 13] 1 is a plot illustrating mixing curves according to various embodiments. [Figure 14]

[0018] 1 is a plot illustrating mixing index and specific energy input versus conductive additive loading according to various embodiments. [Figure 15]

[0019] 1 is a plot illustrating the effect of mixing on certain slurry parameters according to various embodiments. [Figure 16]

[0020] 1 is a plot showing the conductivity of certain slurries as a function of mixing time. [Figure 17A]

[0021] 13A-13C are micrographs of slurries subjected to two different mixing times according to an embodiment. [Figure 17B] 1 is a micrograph of a slurry subjected to two different mixing times according to an embodiment. [Figure 17C] 1 is a micrograph of a slurry subjected to two different mixing times according to an embodiment. [Figure 17D] 1 is a micrograph of a slurry subjected to two different mixing times according to an embodiment. [Figure 18]

[0022] The evolution of the mixing index and conductivity at 100 rpm and mixing duration is shown for two different cathodes. [Figure 19]

[0023] The evolution of the mixing index and conductivity at 100 rpm and mixing duration is shown for two different anode compositions. [Figure 20]

[0024] 1 is a plot showing conductivity as a function of mixing time for two shear conditions according to various embodiments. [Figure 21]

[0025] 1 is a plot showing electrolyte loss with time, mixing duration, and temperature according to various embodiments. [Figure 22]

[0026] 1 is a plot illustrating the effect of temperature on viscosity according to various embodiments. [Diagram 23] 1 is a plot illustrating the effect of temperature on viscosity according to various embodiments. [Figure 24]

[0027] 1 shows the mixing index over time for two different exemplary cathode compositions. [Diagram 25]

[0028] 1 shows the mixing index over time for two different exemplary anode compositions. [Figure 26]

[0029] The mixing index and conductivity of prepared anode compositions using various mixing processes are shown. [Figure 27]

[0030] The mixing index and conductivity are shown for two different cathode compositions prepared using two different mixing methods. [Figure 28]

[0031] 1 shows the mixing index and conductivity of anode compositions mixed at two different mixing times. [Figure 29]

[0032] For the first anode composition, the effect of mixing time on stability during processing is shown. [Diagram 30]

[0033] For the second anode composition, the effect of mixing time on stability during processing is shown. [Diagram 31]

[0034] Two anode compositions and four different mixing durations are shown. [Diagram 32]

[0035] For the first cathode composition, the effect of mixing time during processing on stability is shown. [Diagram 33]

[0036] For the second cathode composition, the effect of mixing time during processing on stability is shown. [Diagram 34]

[0037] Two cathode compositions and three different mixing durations are shown. [Figure 35A]

[0038] 1 shows the capacity of an exemplary semi-solid cathode composition as a function of charge and discharge rate, and sample charge / discharge curves. [Figure 35B]

[0038] The capacity of exemplary semi-solid cathode compositions as a function of charge and discharge rate, and sample charge / discharge curves are shown. [Figure 36A]

[0039] 1 shows the capacity of an exemplary semi-solid cathode composition as a function of charge and discharge rate, and sample charge / discharge curves. [Figure 36B]

[0039] The capacity of exemplary semi-solid cathode compositions as a function of charge and discharge rate, and sample charge / discharge curves are shown. [Figure 37A]

[0040] 1 shows the capacity of an exemplary semi-solid cathode composition as a function of charge and discharge rate, and sample charge / discharge curves. [Figure 37B]

[0040] The capacity of exemplary semi-solid cathode compositions as a function of charge and discharge rate, and sample charge / discharge curves are shown. [Figure 38A]

[0041] 1 shows the capacity of an exemplary semi-solid cathode composition as a function of charge and discharge rate, and sample charge / discharge curves. [Figure 38B]

[0041] The capacity of exemplary semi-solid cathode compositions as a function of charge and discharge rate, and sample charge / discharge curves are shown. [Figure 39A]

[0042] 1 shows the performance of a semi-solid-based electrochemical cell over 100 cycles, and sample charge / discharge curves. [Figure 39B]

[0042] The performance of the semi-solid-based electrochemical cell over 100 cycles and sample charge / discharge curves are shown. [Figure 40A]

[0043] 1 shows the performance of the semi-solid-based electrochemical cell over 30 cycles, and sample charge / discharge curves. [Figure 40B]

[0043] The performance of the semi-solid-based electrochemical cell over 30 cycles and sample charge / discharge curves are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012]

[0044] FIELD OF THE DISCLOSURE Embodiments described herein relate generally to semi-solid suspensions, and in particular to systems and methods for preparing semi-solid suspensions for use as electrodes in electrochemical devices, such as batteries. In some embodiments, a method for preparing a semi-solid electrode includes combining a quantity of an active material with a quantity of an electrolyte to form an intermediate material. The intermediate material is then combined with a conductive additive to form an electrode material. The electrode material is mixed to form a suspension having a mixing index of at least about 0.80, which is then formed into a semi-solid electrode.

[0013]

[0045] Batteries for consumer electronics have been gradually increasing in energy density with the development of lithium-ion batteries. The stored energy or charge capacity of a manufactured battery is a function of (1) the specific charge capacity of the active material (mAh / g) and (2) the volume of the electrodes (cm 3 ) (i.e., the product of the electrode thickness, the electrode area, and the number of layers (stacks)), and (3) the loading of active material in the electrode medium (e.g., 1 cm 3 Therefore, in general, to improve commercial attractiveness (e.g., increase energy density and reduce cost), the areal charge capacity (mAh / cm) of the electrode must be increased. 2 It is desirable to increase the areal charge capacity (A / A) of the electrode. One way to achieve increased areal charge capacity, and therefore reduce the relative percentage of inactive components, is to increase the thickness of the electrode. However, conventional electrode compositions using binders cannot be made thicker than about 200 μm because conventional electrodes manufactured using casting and high speed roll-to-roll calendering processes tend to crack and / or delaminate when dried from a flat current collector if made thicker than 200 μm. Thicker electrodes also result in higher cell impedance, which reduces energy efficiency (e.g., as described in Yu et al., "Effect of electrode parameters on LiFePO4 cathodes," J. Electrochem. Soc. Vol. 153, A835-A839 (2006)).

[0014]

[0046] Embodiments of the semi-solid electrode compositions and preparation methods described herein can be produced directly in a semi-solid suspension, thereby avoiding all of the traditional binder and electrode casting, drying, and calendaring steps. Some advantages of this method include, for example, (i) simplified production with a reduced amount of equipment (i.e., less capital intensive), (ii) the ability to produce electrodes of various thicknesses (e.g., by simply changing the dimensions of the mold), and (iii) the ability to produce electrodes of thicker thicknesses (>200 μm) and higher capacity (mAh / cm 2 ) fabricating an electrode, thereby reducing the volume, mass, and cost distribution of inactive components relative to the active material; and (iv) omitting binders (e.g., PVdF), thereby reducing the tortuosity of the electrode, increasing ionic conductivity, and increasing safety by eliminating binders that can contribute to exothermic reactions. Examples of battery constructions using semi-solid suspensions are described in International Patent Publication No. WO2012 / 024499, entitled "Stationary, Fluid Redox Electrode," International Patent Publication No. WO2012 / 088442, entitled "Semi-Solid Filled Battery and Method of Manufacture," U.S. Patent Application No. 13 / 607,021, entitled "Stationary Semi-Solid Battery Module and Method of Manufacture," and U.S. Patent Application No. 13 / 606,986, entitled "Semi-Solid Electrode Cell Having a Porous Current Collector and Methods of Manufacture," the entire disclosures of each of which are incorporated herein by reference.

[0015]

[0047] The term "about" as used herein generally means ±10% of the stated value, e.g., about 5 includes 4.5-5.5, about 10 includes 9-11, about 100 includes 90-110, etc.

[0016]

[0048] Although the embodiments described herein generally relate to electrochemical devices, such as, for example, lithium ion batteries, the systems, methods, and principles described herein are applicable to any device that contains an electrochemically active medium. In other words, any electrode and / or device that includes at least an active material (a source or sink of charge carriers), an electronically conductive additive, and an ionically conductive medium (electrolyte), such as a battery, a capacitor, an electric double layer capacitor (e.g., ultracapacitor), a pseudocapacitor, etc., falls within the scope of the present disclosure.

[0017]

[0049] In some embodiments, a method of preparing a semi-solid electrode (also referred to herein as a "semi-solid suspension" and / or "slurry" electrode) can include combining an amount of active material with an amount of electrolyte to form an intermediate material. The intermediate material is combined with the electrolyte to form the electrode material. The electrode material is mixed until a substantially stable suspension is formed having a mixing index of at least about 0.8, at least about 0.9, at least about 0.95, or at least about 0.975, inclusive of all ranges therebetween. In some embodiments, the electrode material is mixed until a substantially stable suspension is formed having a mixing index of at least about 10, inclusive of all ranges therebetween. -6 S / cm, at least about 10 -5 S / cm, at least about 10 -4 S / cm, at least about 10 -3 S / cm, or at least about 10 -2 The electrode material is mixed until it has a conductivity of about 1,000 s / cm, inclusive of all ranges therebetween. -1The electrode material is mixed until it has an apparent viscosity of less than about 100,000 Pa-s, less than about 10,000 Pa-s, or less than about 1,000 Pa-s at an apparent shear rate of 100 / 200 / s. In some embodiments, the amount of active material in the electrode material can be about 20% to about 75% by volume, about 40% to about 75% by volume, or about 60% to about 75% by volume, inclusive of all ranges therebetween. In some embodiments, the amount of electrolyte in the electrode material can be about 25% to about 70% by volume, about 30% to about 50% by volume, or about 20% to about 40% by volume, inclusive of all ranges therebetween. In some embodiments, the amount of conductive material in the electrode material can be about 0.5% to about 25% by volume, or about 1% to about 6% by volume, inclusive of all ranges therebetween.

[0018]

[0050] In some embodiments, the mixing of the electrode materials can be performed, for example, in one of a high shear mixer, a planetary mixer, a centrifugal planetary mixer, a sigma mixer, a CAM mixer, and / or a roller mixer. In some embodiments, the mixing of the electrode materials can provide a specific mixing energy of at least about 90 J / g, at least about 100 J / g, between about 90 J / g and about 150 J / g, or between about 100 J / g and about 120 J / g, including all ranges therebetween.

[0019]

[0051] In some embodiments, the electroactive material of the positive electrode of the lithium system comprises the general family of ordered rock-salt compounds LiMO2, including α-NaFeO2 (so-called "layered compounds"), or the orthorhombic LiMnO2 structure type, or derivatives thereof with different crystal symmetries, crystal arrangements, or partial substitution of metal or oxygen. M comprises at least one first row transition metal, but may also comprise non-transition metals, including, but not limited to, Al, Ca, Mg, or Zr. Examples of such compounds include LiCoO2, Mg-doped LiCoO2, LiNiO2, Li(Ni,Co,Al)O2 (known as "NCA"), and Li(Ni,Mn,Co)O2 (known as "NMC"). Other families of exemplary electroactive materials include spinel structures such as LiMn2O4 and its derivatives, where the structure contains nanoscopic domains with ordered halite and spinel arrangements, so-called "layered spinel nanocomposites," olivine LiMPO4 and its derivatives, where M contains one or more of Mn, Fe, Co, or Ni, partially fluorinated compounds such as LiVPO4F, other "polyanionic" compounds as described below, and VO and VO. 11 Vanadium oxide containing V x O y Includes:

[0020]

[0052] In some embodiments, the active material comprises a transition metal polyanion compound, such as those described in U.S. Patent No. 7,338,734. In one or more embodiments, the active material comprises an alkali metal, transition metal oxide or phosphate, e.g., the compound is an A x (M' 1-a M” a )y(XD4) z , A x (M' 1-a M” a )y(DXD4) z , or A x (M' 1-a M” a )y(X2D7) zor the compound has a composition of matter such that x multiplied by y(1-a) and by one or more formal valences of M' and ya multiplied by the formal valence or valences of M" are equal to z multiplied by the formal valence of the XD4, X2D7, or DXD4 group; or the compound has a composition of matter such that x multiplied by y(1-a) and by one or more formal valences of M' and by ya multiplied by the formal valence or valences of M" are equal to z multiplied by the formal valence of the XD4, X2D7, or DXD4 group; 1-a M” a ) x M' y (XD4) z , (A 1-a M” a ) x M' y (DXD4) z (A 1-a M” a ) x M' y (X2D7) z (1-a) x has a value such that the quantity ax, added to one or more formal valences of M", and y, added to one or more formal valences of M', is equal to z multiplied by the formal valences of the XD4, X2D7, or DXD4 groups. In the compound, A is at least one of an alkali metal and hydrogen, M' is a first row transition metal, X is at least one of phosphorus, sulfur, arsenic, molybdenum, and tungsten, M" is any of the metals of Groups IIA, IIIA, IVA, VA, VIA, VIIA, VIIIA, IB, IIB, IIIB, IVB, VB, and VIB, and D is at least one of oxygen, nitrogen, carbon, or halogen. The positive electroactive material may be the compound LiMPO4 with an olivine structure, where M is one or more of V, Cr, Mn, Fe, Co, and Ni, and the compound is optionally doped at the Li, M, or O sites. Deficiencies at the Li sites are compensated for by the addition of a metal or metalloid, and deficiencies at the O sites are compensated for by the addition of a halogen. In some embodiments, the positive active material is thermally stable and has an olivine structure, and is (Li 1-x l x)It has the formula of NPO4 and contains a transition metal-doped lithium transition metal phosphate, where M is one or more of V, Cr, Mn, Fe, Co, and Ni, Z is a non-alkali metal dopant such as Ti, Zr, Nb, Al, or Mg, and x ranges from 0.005 to 0.05.

[0021]

[0053] In some embodiments, the lithium transition metal phosphate material is L 1-x-z M 1+z has the overall composition of PO4, where M contains at least one first-row transition metal selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, and Ni, x ranges from 0 to 1, and z can be positive or negative. M contains Fe and z is between about 0.15 and -0.15. The material can exhibit a solid solution over the composition range of 0 < x < 0.15, or the material can exhibit a stable solid solution over the composition range of x between 0 and at least about 0.05, or the material can exhibit a stable solid solution over the composition range of x between 0 and at least about 0.07 at room temperature (22 - 25 °C). The material can also exhibit a solid solution in regions where lithium is insufficient, such as when x ≥ 0.8, or x ≥ 0.9, or x ≥ 0.95.

[0022]

[0054] In some embodiments, the redox-active electrode material includes metal salts that accumulate alkali ions by undergoing a substitution or conversion reaction. Examples of such compounds include metal oxides, such as CoO, Co3O4, NiO, CuO, MnO, which are typically used in the negative electrodes of lithium batteries, and which, upon reaction with Li, undergo a substitution or conversion reaction to form a mixture of Li2O and metal components in the form of further reduced oxides or metallic forms. Other examples include metal fluorides, such as CuF2, FeF2, FeF3, BiF3, CoF2, and NiF2, which undergo a substitution or conversion reaction to form LiF and reduced metal components. Such fluorides can be used as the positive electrodes of lithium batteries. In other embodiments, the redox-active electrode material includes carbon monofluoride or a derivative thereof. In some embodiments, the material that has undergone the substitution or conversion reaction is in the form of particulates having an average size of 100 nanometers or less. In some embodiments, the material that has undergone the substitution or conversion reaction includes a nanocomposite of the active material mixed with an inert host.

[0023]

[0055] In some embodiments, the slurry components can be mixed in a batch process, for example in a batch mixer, which can include, for example, a high shear mixer, a planetary mixer, a centrifugal planetary mixer, a sigma mixer, a CAM mixer, and / or a roller mixer, with the components being added in a particular spatial and / or temporal order as described in more detail herein. In some embodiments, the slurry components can be mixed in a continuous process (for example in an extruder) with the components being added in a particular spatial and / or temporal order.

[0024]

[0056] In some embodiments, process conditions (temperature, shear rate or rate schedule, order of addition of ingredients, location, and speed, mixing or residence time) can be selected and / or modified to control the electrical, rheological, and / or compositional (e.g., homogeneity) properties of the prepared slurry. In some embodiments, the speed of the mixing elements (e.g., roller blade edges) can be between about 0.5 cm / sec and about 50 cm / sec. In some embodiments, the minimum gap through which fluids flow during a mixing event (e.g., distance from the roller blade edges to the containment wall of the mixer) can be between about 0.05 mm and about 5 mm. Thus, the shear rate (velocity scale divided by length scale) can be between about 1 and about 10,000 s . -1 In some embodiments, the shear rate is between 1 s -1 In other embodiments, the number of -1 Exceeds.

[0025]

[0057] In some embodiments, the process conditions can be selected to produce a prepared slurry having a mixing index of at least about 0.80, at least about 0.90, at least about 0.95, or at least about 0.975. In some embodiments, the process conditions can be selected to produce a prepared slurry having a mixing index of at least about 10 -6 S / cm, at least about 10 -5 S / cm, at least about 10 -4 S / cm, at least about 10 -3 S / cm, or at least about 10 -2 In some embodiments, the process conditions can be selected to produce a prepared slurry having an apparent viscosity of less than about 100,000 Pa-s, less than about 10,000 Pa-s, or less than about 1,000 Pa-s, all less than 1,000 s / cm at room temperature. -1 In some embodiments, the process conditions can be selected to produce a conditioned slurry having two or more properties as described herein.

[0026]

[0058] Mixing and forming the semi-solid electrode typically includes (i) conveying and / or feeding the raw materials, (ii) mixing, (iii) conveying the mixed slurry, (iv) dispensing, and (v) forming. In some embodiments, multiple steps of the process can be performed simultaneously and / or on the same piece of equipment. For example, mixing and conveying the slurry can be performed simultaneously in an extruder. Each step of the process can include one or more possible embodiments. For example, each step of the process can be performed manually or on any of a variety of process equipment. Each step can also include one or more sub-processes and, optionally, inspection steps to monitor the quality of the process.

[0027]

[0059] Conveying and / or feeding of the raw materials can include manual metering of materials in batches with natural feeding (e.g., allowing the mixer to accept the materials to be mixed without any external force), manual metering of materials in batches with force feeding via a piston mechanism or screw type "side stuffer", gravimetric screw solids feeders that naturally feed (e.g., feeding at a rate at which the mixer can naturally accept the materials), gravimetric screw solids feeders that force feed (e.g., a combination of a unit sold by Brabender Industries Inc. with a piston mechanism or screw type "side stuffer"), and / or any other suitable conveying and / or feeding method and / or any suitable combination thereof.

[0028]

[0060] In some embodiments, for example after mixing, the slurry can be conveyed and / or pressurized using, for example, a piston pump, a peristaltic pump, a gear / lobe pump, a single screw pump, a single screw extruder, a conveying section of a twin screw extruder, and / or any other conveying device. In some embodiments, during conveying and / or pressurization, the torque and / or power of the conveying device, the conveying device outlet pressure, flow rate, and / or temperature can be measured, monitored, and / or controlled.

[0029]

[0061] In some embodiments, for example after conveying and / or pressing, the slurry can be dispensed and / or extruded using, for example, a "hanger die" sheet extrusion die, a "winter manifold" sheet extrusion die, a profile style sheet extrusion die, any nozzle operable to apply a continuous stream of material to a substrate, pouring into a precisely sized and shaped mold (e.g., filling pockets with material), and / or any other dispensing device.

[0030]

[0062] In some embodiments, after dispensing, the slurry can be formed into a final electrode. For example, the slurry can be formed with calendaring rolls, punched and / or pressed, shaken and / or cut into separate sections. Also, in some embodiments, undesired portions of the material can be removed (e.g., masked and cleaned) and optionally recycled back into the slurry manufacturing process.

[0031]

[0063] The systems, mixing equipment, processes and methods described herein can be used to produce semi-solid suspensions (e.g., slurries) suitable for use in electrochemical devices (e.g., batteries). The semi-solid suspensions produced by such systems and methods are suitable for formulating slurry-based electrodes with specific properties, such as flowability, electrical conductivity, and electrochemical performance. For example, some suitable mixing devices include batch mixers, such as higher shear mixers, planetary mixers, centrifugal planetary mixers, sigma mixers, CAM mixers or roller mixers, CW Brabender or Banburry® style mixers, continuous compounding devices, such as ported single or twin screw extruders (e.g., Leistritz, Haake), high shear mixers, such as blade blenders, high speed kneaders, and / or rotating impellers. In some embodiments, the mixing device can be operable to control the flowability of the slurry to adjust the temperature and / or control the homogeneity of the slurry by adjusting the chemical composition.

[0032]

[0064] In embodiments where a batch mixer is used to mix the semi-solid suspension, the semi-solid suspension may be transferred from the batch mixer to another piece of processing equipment, such as an extruder. In such embodiments, the transfer method may be selected to minimize electrolyte loss, not appreciably disrupt the slurry state, and / or not introduce other processing difficulties, such as the entrainment of ambient gases. In embodiments where an extruder (e.g., twin screw) is used to mix the semi-solid suspension, mixing and material conveying may be performed together, thus eliminating one process step.

[0033]

[0065] In some embodiments, some electrolyte loss can be tolerated and used as a control specification, with the tolerable amount typically decreasing as the volume fraction of electrolyte increases and / or the mixing index increases. For example, at a mixing index of 0.8, the maximum electrolyte loss can be controlled to be less than about 39%, less than about 33%, or less than about 27%. At a mixing index of 0.9, the maximum electrolyte loss can be controlled to be less than about 5%, less than about 4%, or less than about 3%. At mixing indices higher than 0.9, the maximum electrolyte loss can be controlled to be less than about 5%, less than about 4%, or less than about 3%. Component concentrations can be calculated to determine and / or predict acceptable losses and can vary depending on the particular component. In other embodiments, the loss tolerance is higher, while in others it is more restrictive.

[0034]

[0066] In some embodiments, the slurry composition and mixing process can be selected to homogeneously disperse the components of the slurry, achieve a conductive percolation network and sufficiently high bulk conductivity throughout the slurry that correlates with desirable electrochemical performance as described in further detail herein, and obtain a rheological state conducive to processing, including transport, conveying (e.g., extrusion), dispensing, segmenting or cutting, and post-dispensing shaping (e.g., pressing, rolling, calendaring, etc.), or any combination thereof.

[0035]

[0067] For example, FIG. 1 shows the electrical conductivity of various slurry formulations, and FIG. 2 shows the yield stress, rheological parameters of the same slurry formulations prepared using various mixing methods, such as high shear mixing, planetary mixing, ultrasonic planetary mixing, hand mixing, and ultrasonic hand mixing. As shown in FIG. 1 and FIG. 2, there can be significant variations in electrical conductivity and yield stress of the slurry formulations when prepared using various mixing methods, demonstrating that the mixing method can affect at least some of the properties and / or performance criteria of the various slurry formulations. In some embodiments, the mixing method can be selected to obtain one or more desired properties of the final adjusted slurry. In some embodiments, maximizing a performance criterion is not always the most desirable property of the final adjusted slurry. In other words, while it is usually desirable to produce a slurry with high electrical conductivity, if the final slurry is not easily formable and / or stable, the high electrical conductivity of that particular slurry will not be advantageous. Similarly, it is not desirable to produce a slurry that is easily formable and / or very stable, but has low electrical conductivity.

[0036]

[0068] During mixing, the compositional homogeneity of the slurry generally increases with mixing time, but the microstructure of the slurry may also change. The compositional homogeneity of a slurry suspension can be quantitatively evaluated by experimental methods based on measuring the statistical variation of the concentration distribution of the components of the slurry suspension. For example, the mixing index is a statistical measure, essentially a normalized variance or standard deviation, that indicates the degree of compositional homogeneity. (See, for example, Erol, M and Kalyon, DM, Assessment of the Degree of Mixedness of Filled Polymers, Intern. Polymer Processing XX (2005) 3, pps. 228-237). Complete separation would have a mixing index of zero, and completely homogeneous mixing would have a mixing index of 1. Alternatively, the homogeneity of the slurry can be expressed as a compositional homogeneity (+x% / -y%), which is defined herein as (100%-c). * From C (100%+x) *The range of x and Y values ​​is therefore defined as the range of x and Y values ​​that are bounded by the samples that exhibit the greatest positive and negative deviations from the average value C, and therefore all the composite material sample compositions obtained fall within this range.

[0037]

[0069] The basic process of determining the mixing index involves taking several equal and appropriately sized material samples from the agglomerated mixture and performing compositional analysis on each sample. Sampling and analysis can be repeated at various times during the mixing process. The size and volume of the samples are based on length scale considerations, where homogeneity is important, such as a multiple of both the maximum solid particle size and the ultimate mixed state average intraparticle distance at the lower end, and 1 / N of the total volume, where N is the number of samples at the upper end. Optionally, the samples can be on the order of the electrode thickness, which is typically much smaller than the length and width of the electrodes. The capacity of certain laboratory equipment, such as a thermogravimetric analyzer (TGA), further narrows the range of practical sample volumes. The "dimension" of the sample refers to the cube root of the sample volume. For example, a common approach to verify sampling (number of samples) is that the average composition of the samples corresponding to any mixing duration matches the overall portion of the material components introduced into the mixer to a certain tolerance. The mixing index at a given mixing time is calculated according to this embodiment as 1-σ / σ ref where σ is the standard deviation in the measured composition (which may be a measured amount of any one or more components of the slurry), and σ ref is [C(1-C)] 1 / 2where C is the average composition of N samples such that the variation in sample composition decreases and the mixing index approaches 1. In the above description, it should be understood that "time" and "duration" are general terms that describe the progress of a mixing event. Other mixing indicators can be used to predict or estimate how well a slurry will be mixed, such as, for example, the cumulative energy input to the mixture, the number of armatures, rotations of rollers, mixing blades, or screws, the distance traveled by a theoretical point or actual microparticles in the mixture, the mixing temperature (affected by viscous heating), certain dimensionless numbers commonly used in engineering analysis, and others.

[0038]

[0070] In one embodiment, a sample containing 50% active material powder by volume in an organic solvent with a particle size distribution of D50=10 μm and D90=15 μm, and 6% conductive additive agglomerates by volume with D50=8 μm and D90=12 μm, with a total volume of 43 cubic centimeters is prepared. This mixture is used to prepare a sample having an area of ​​80 cm 2 For this purpose, an electrode with a thickness of 500 μm can be constructed. The sample dimensions must be a certain multiple larger than the size of the larger solid particles, i.e. 15 μm, and the intraparticle length scale of the larger mixed states, i.e. about 16 μm. For a target of N=14 samples, the sample dimensions must be less than 2,500 μm. The particular dimension of symmetry is in the middle of this range, i.e. 500 μm. Thus, to determine the quantity of the mixing index, the samples are taken with a special tool having a cylindrical sampling cavity with a diameter of 0.5 mm and a depth of 0.61 mm. In this example, the sample volume is 0.12 mm. 3 It becomes.

[0039]

[0071] In some embodiments, the selection of the sample volume for measuring the mixing index follows the length scale for which uniformity is important. In some embodiments, this length scale is the thickness of the electrode on which the slurry is used (e.g., 250 μm to 2,000 μm). For example, if the electrode is 0.5 mm thick, the sample volume is (0.5 mm) 3 =0.125mm 3About 0.04 mm 3 and about 0.4 mm 3 If the electrode is 0.2 mm thick, the sample volume is preferably between 0.0025 mm 3 and 0.025mm 3 If the electrode is 2.0 mm thick, the sample volume is preferably between 2.5 mm 3 and 25mm 3 In some embodiments, the sample volume when evaluating the mixing index is the cube of the electrode thickness ±10%. In some embodiments, the sample volume when evaluating the mixing index is 0.12 mm 3 ±10%. In one embodiment, the mixing index is measured by drawing N samples from a batch of electrode slurry or from a formed slurry electrode having a volume greater than the total volume of the N samples, where N is at least 9 and each sample has a sample volume. Each sample volume is heated in a thermogravimetric analyzer (TGA) with flowing oxygen gas according to a time-temperature profile, held at room temperature for 3 minutes, then heated at 20°C / min to 850°C, and the cumulative weight loss between 150°C and 600°C is used to calculate the mixing index. The electrolyte solvent measured in this manner is evaporated and the measured weight loss is primarily due to the thermal decomposition of carbon in the sample volume.

[0040]

[0072] In some embodiments, the slurry can be mixed at 30-100 rpm using a Brabender Batch Mixer. In some embodiments, the slurry can be mixed at 10-200 rpm or any other suitable speed. In some embodiments, the speed of the mixer can be varied throughout the mixing cycle, for example, the mixing speed can be reduced to incorporate the components and the mixing speed can be increased to homogenize the slurry. In some embodiments, the mixing speed can be varied during the addition of the components. In some embodiments, the total mixing time can be between 1 minute and 100 minutes. In other embodiments, any suitable mixing time can be selected. In some embodiments, the mixer can provide a specific mixing energy between 3 J / g and 2,000 J / g. In other embodiments, the mixer can provide any suitable amount of mixing energy.

[0041]

[0073] As described herein, the conductive additive can have technical properties and morphology (i.e., hierarchical clustering of elementary particles) that affect its dispersion and electrochemical behavior in dynamic and / or static suspensions. Properties that can affect the dispersion and electrochemical behavior of the conductive additive include surface area and bulk conductivity. For example, in the case of certain conductive carbon additives, morphological factors can affect the dispersion of carbon particles. The primary carbon particles have dimensions on the order of nanometers, and the particles typically exist as elements of larger aggregates made up of particles that are electrically bonded (e.g., by van der Waals forces) or sintered together. Such aggregates can have dimensions on the order of nanometers to microns. Also, depending on the surface energy of the particles, the environment, and / or the temperature, the aggregates can form larger scale clusters, commonly referred to as agglomerates, which can have dimensions on the order of several microns to tens of microns.

[0042]

[0074] When such conductive additives are included in the slurry, fluid shear forces, such as those applied during mixing, can disrupt the carbon network, for example by overcoming the binding forces of the agglomerates and aggregates. By disrupting the conductive network, the additives can exist in a finer scale (more granular, more homogeneous) dispersion of the conductive solids. Mixing can also densify clusters of the conductive solids. In some embodiments, mixing can both disrupt the conductive network and densify the clusters, which can disconnect the conductive pathways and adversely affect electrochemical performance.

[0043]

[0075] 3A-3C are schematic diagrams of an electrically active slurry containing active material 310 and conductive additive 320, where the amount of conductive additive 320 is not sufficient to form a conductive network. FIG. 3A shows the slurry before any mixing energy has been applied or after only minimal mixing energy has been applied. FIG. 3B shows the slurry with an optimal amount of mixing energy applied. FIG. 3C shows the slurry with an excessive amount of mixing energy applied. As shown in FIG. 3B, even with the optimal amount of mixing, the amount of conductive additive 320 is not sufficient to produce a discernible conductive network throughout the electrode volume.

[0044]

[0076] 4A-4C are schematic diagrams of an electroactive slurry containing active material 410 and conductive additive 420. In contrast to FIGS. 3A-3C, in this example, the amount of conductive additive 420 is sufficient to form a conductive network. As shown in FIG. 4A, the conductive additive 420 is mostly in the form of unbranched agglomerates 430. The homogeneity of the conductive additive 420 can be characterized as inhomogeneous at this stage. As shown in FIG. 4B, the agglomerates 430 have been "broken down" by fluid shear and / or mixing forces, creating the desired "wiring" (also referred to herein as "conductive pathways") of the interparticle network of conductive additive agglomerates 440. As shown in FIG. 4C, the conductive network has been disrupted by overmixing, where the conductive additive 420 is now in the form of broken and / or incomplete (or non-conductive) pathways 450. 3A-3C and 4A-4C thus show that an electrochemically active slurry can include a minimum threshold of conductive additive 320 / 420 loading and an optimal processing regime between the two extremes (i.e., the slurry shown in FIG. 4B). By selecting an appropriate loading and processing regime of conductive additive 320 / 420, a semi-solid suspension can be formed that has a discernible conductive interparticle network (e.g., a network of conductive additive agglomerates 440). In some embodiments, the specific mixing energy applied can be from about 90 J / g to about 150 J / g, e.g., at least about 90 J / g, at least about 100 J / g, at least about 120 J / g, or at least about 150 J / g, inclusive of all ranges therebetween.

[0045]

[0077] The amount of conductive additive used in a given mix relative to other ingredients, such as active materials, that is appropriate for the mix to achieve a particular level of bulk conductivity, i.e., the mass or volume fraction of the conductive additive (also referred to herein as the "loading" of the conductive additive), depends on the cluster state. The conductive additive loading can be selected using percolation theory. Referring now to FIG. 5, a plot of electrochemical slurry conductivity versus conductive additive loading is shown. As the conductive additive loading increases, the conductivity of the slurry also increases. Three regions of conductivity are depicted in FIG. 5. At low loadings of conductive additive 522, the slurry has a relatively low conductivity. For example, this slurry with low conductive additive loading 522 can correspond to the slurry depicted in FIGS. 3A-3C, where there is insufficient conductive material to form a discernible interparticle network. As the conductive additive loading increases, a percolation network 524 begins to form because the conductive additive chains can provide connectivity at least between the active particles. As the loading is further increased (e.g., as shown in the slurries depicted in Figures 4A-4C), a relatively stable interparticle network 530 is formed. The shape and height of the percolation curve can be tuned by the method of compounding the properties of the conductive additive as described herein.

[0046]

[0078] However, the amount of conductive additive used in the slurry may be constrained by other considerations. For example, it is usually desirable to maximize battery attributes such as energy density and specific energy, and active material loading directly impacts these attributes. In a similar vein, in addition to the conductive material loading, the amount of other solids, such as active material, must be considered. The slurry composition and mixing process described herein can be selected to obtain a slurry of relatively uniform composition while allowing for clustering of the conductive additive to improve electrical conductivity. That is, the slurry can be formulated and mixed such that a minimum threshold amount of conductive additive is included to form an interparticle network after an appropriate amount of mixing, thereby maximizing active material loading. In some embodiments, the amount of conductive additive in the slurry can be about 0.5% to about 25% by volume, such as about 0.5%, 1%, 6%, or 25% by volume, inclusive. In some embodiments, the electronic conductivity of the prepared slurry is at least about 10%, inclusive of all ranges therebetween. -6 S / cm, at least about 10 -5 S / cm, at least about 10 -4 S / cm, at least about 10 -3 S / cm, or at least about 10 -2 S / cm.

[0047]

[0079] In some embodiments, the maximum conductive additive loading at zero active material loading and the maximum active material loading at zero conductive additive loading depend on the type of conductive additive and active material used. For example, a linear trend of active material versus conductive additive with a constant rheological parameter value (e.g., effective viscosity at a given shear rate) is usually observed, although other shapes (with outward curvature, inward curvature, or inflection points) are possible. In other words, a constant rheological parameter value can define a region within which a "workable" composition can be selected. This region can depend, for example, on the materials used and can also be determined experimentally. In some embodiments, a workable composition is one that has a surface area of ​​40 m 2 / g, approximately 20% or less of the conductive additive by volume, and a surface area of ​​1,000 m2 / g and about 5% or less of the conductive additive by volume, and about 52% or less of the lithium titanate by volume with a tap density of 1.3 g / cc.

[0048]

[0080] In some embodiments, it is desirable for the electrochemically active slurry to be "processable" to facilitate material handling associated with battery manufacturing. For example, if the slurry is too fluid, it may become compositionally unstable; that is, it may lose homogeneity when exposed to certain forces, such as gravity (e.g., settling of solids) or centrifugal forces. If the slurry is unstable, density differences or other attributes of the solid phases may cause separation and / or compositional gradients. In other words, if the slurry is too fluid, which may result from low solids loading or a significantly disrupted conductive network, the solids may not be sufficiently bound in place to prevent particle movement. Alternatively, if the electrochemically active slurry is too solid, the slurry may decompose, disintegrate, and / or otherwise separate into pieces, which may complicate processing and dimensional control. Formulating the slurry within a zone of sufficient processability can facilitate easier slurry-based battery manufacturing. The processability of the slurry can usually be quantified using rheological parameters that can be measured using a rheometer. Some examples of different types of rheometers that can be used to quantify the processability of a slurry include strain or stress controlled rotational, capillary, slit, and extensional rheometers.

[0049]

[0081] As described herein, the mixing speed (which can be fixed, stepped, continuously variable, oscillating, and / or controlled according to a feedback signal) and duration of mixing (or a particular step) can affect the establishment and stability of electrical conductivity of the carbon substrate and the corresponding cell voltage efficiency, as well as the compositional homogeneity among all material components. The establishment and stability of electrical conductivity may be degraded by high shear or long mixing times. However, high shear and / or long mixing times can promote homogeneity, which can aid in local electrode equilibration and long cycle life. Also, the "processability" of the material and / or the long term local compositional stability (e.g., no "settling" of solids in the finished electrode), which can enable more efficient processing and handling during manufacturing, can be affected by the mixing speed and duration.

[0050]

[0082] Feeding of ingredients into a mixer, extruder, or other combining equipment can be facilitated by a ram feed chute or similar constant volume device. The rate at which ingredients are fed into the combining equipment can be set or controlled, which can limit the accumulated shear history of the materials added first.

[0051]

[0083] Active materials and conductive additives of different types, structures, morphologies, and / or made by different processes can have different interactions with the various components in the mixture, resulting in slurries that have the same ratio of solids and electrolyte with different rheological properties.

[0052]

[0084] In some embodiments, the ratio of active material to conductive additive to electrolyte may affect the stability, processability and / or rheological properties of the slurry. Figures 6A-6C show electrode slurry mixtures with different loadings of active material and conductive additive to electrolyte. Low loading 610 (Figure 6A), i.e., a slurry with relatively low active material and conductive additive to electrolyte, may result in an unstable or "runny" mixture. As shown, phase separation, i.e., separation of active material and conductive additive (solid phase) from electrolyte (liquid phase), can be observed in the low loading 610 mixture. In contrast, at high loading mixture 630 (Figure 6C), where the maximum packing of solid material in electrolyte is exceeded, the mixture becomes overly dry and is not sufficiently fluid to be transferred or processed into a desired shape or thickness. Thus, as shown in Figure 6B, there is an optimal loading mixture 620 where the slurry is stable (i.e., the solid particles are maintained in suspension) and is sufficiently fluid to be processable into an electrode.

[0053]

[0085] "Processable" slurries with various solid loadings can be evaluated for flow and processability. The rheological behavior of the slurry can indicate processability in flow under pressure such as single or twin screw extrusion and / or flow through a die. The slurries can be classified as "suspensions" with various loading levels and low viscosity liquid media / substrates. The flow behavior of such suspensions can depend on the size distribution, shape and volume fraction of the solid particles, inter-particle and particle-substrate interactions, and the flowability of the substrate. In some embodiments, slurries can be selected based on rheological properties, which can be used to predict the preferred processability and / or desired electrochemical performance of the slurry. The rheological properties of "processable" slurries can be determined by compositional formulation, e.g., different active materials and conductive additives loaded at various concentrations, and / or homogeneity of the slurry.

[0054]

[0086] In some embodiments, the type and loading level of conductive additive can be selected that can form a gel-like network that holds the suspension together and prevents separation. At this loading level, depending on its structure, various types of conductive additives can form slurries with different rheological properties at the same loading level. Alternatively, different amounts and / or types of conductive additives can be packed into a slurry that can have the same rheological properties at a given volume loading level of active material. Similarly, the type of active material incorporated into the conductive additive for a given volume loading level and type of formulation can affect the rheological properties of the slurry. Also, the particle size, aspect ratio, and particle size distribution of the solids (e.g., active material and / or conductive additive) can affect the rheological properties of the slurry.

[0055]

[0087] In some embodiments, the conductive additive can affect the rheological properties of the suspension. Thus, in such embodiments, at the same loading level of conductive additive, increasing the concentration of active material can contribute to the rheological properties of the slurry by increasing the shear viscosity of the suspension. FIG. 7 shows the apparent viscosity (η) for various compositions of slurries formulated from about 35% to about 50% NMC by volume and about 6% to about 12% conductive additive C45 by volume. appr Pa-s) and apparent shear rate (γ appr s -1 8 shows the rheological properties described herein for various compositions of slurries formulated from about 35% to about 50% by volume of graphite (PGPT) and about 2% to about 10% by volume of conductive additive C45. The apparent viscosity of the slurries described herein decreases as the apparent shear rate increases.

[0056]

[0088] A capillary rheometer can be used to characterize the rheological behavior of slurries of various compositions. A capillary rheometer uses pressure-induced flow to force a material through a 10 -1 s -1For example, the processability of a suspension is determined by subjecting it to higher shear rates. In a capillary rheometer, the suspension in a reservoir / barrel is allowed to flow through a capillary / die with pressure generated by a piston. The flow and deformation behavior of the suspension can be characterized by using various capillary dies with different diameters, lengths and entrance angles to generate flow rate vs. pressure drop data.

[0057]

[0089] Suspension flow can be exhibited by a variety of mechanisms depending on the suspension properties, i.e., yield stress, matrix viscosity, loading level, particle interactions, and wall slip behavior controlled by such properties. In some embodiments, suspensions can flow with or without slip. In some embodiments, suspensions can flow like a plug without deformation at stresses below the yield stress. Highly loaded slurry suspensions can be characterized by strong slip mechanisms and high yield stresses of approximately 35,000 Pa.

[0058]

[0090] Slurry suspensions, when flowing at critical shear stress values ​​due to low viscosity of the liquid matrix in the composition, may exhibit a tendency to separate and flow instabilities, structure development, mat formation and / or binder filtration. Such behavior can be characterized by using a capillary rheometer using a small diameter and long L / D. The composition formulation, particularly the level of conductive carbon loading, and the extrusion temperature can affect such structural changes during flow under pressure. Figures 9 and 10 show time-pressure graphs for various formulations of a first slurry containing about 35%-50% NMC and about 6%-12% C45 (Figure 9) and various formulations of a second slurry containing about 45%-50% PGPT and about 2%-6% C45 (Figure 10). As illustrated here, depending on the rheological properties of the slurry, such as the apparent viscosity and apparent shear rate, various amounts of pressure are required to dispense or flow a predefined amount of the slurry within a given period of time. In some embodiments, the pressure is increased by about 1,000 s. -1The apparent viscosity of the slurry prepared at an apparent shear rate of 100,000 Pa-s, 10,000 Pa-s, or 1,000 Pa-s can be less than about 100,000 Pa-s. In some embodiments, the inverse of the average slurry viscosity can be greater than about 0.001 L / (Pa-s). Some slurry formulations include three major components, such as an active material (e.g., NMC, lithium iron phosphate (LFP), graphite, etc.), a conductive additive (e.g., carbon black), and an electrolyte (e.g., a mixture of a carbonate-based solvent and a dissolved lithium-based salt). In some embodiments, the three major components are mixed in a batch mixer. In some embodiments, the active material is added to the mixing bowl first, followed by the solvent. In some embodiments, the electrolyte can be homogenously mixed with the dense active material to form an intermediate material without experiencing any "blackout" of material from the mixing section of the mixing bowl. When the solvent and active material are thoroughly mixed, a loose, moist paste can be formed. A conductive additive can be added to this intermediate material (i.e., a loose paste) so that it can be uniformly incorporated into the mixture. In some embodiments, the active material may have a tendency not to clump together into clumps. In other embodiments, the ingredients can be combined in a different order of addition, for example, the solvent can be added to the mixing bowl first, then the active material, and finally the additives. In other embodiments, any other order of addition can be used to mix the slurry.

[0059]

[0091] Mixers (e.g., batch mixers) can apply dispersive shear energy to the bulk material being mixed. The mixing energy can be normalized to the mass of the material being mixed, which can provide a quantifiable metric for the amount of work done to mix a given sample. As mixing progresses over time, the mixing energy increases. If a relatively small amount of mixing energy is added to the slurry at the beginning of the mixing operation, the mixture may exhibit low homogeneity, e.g., the material may not be distributed evenly throughout the mass of the mixture. Also, slurries to which a relatively small amount of mixing energy has been added may have low flowability and / or formability. For example, if the liquid phase of the mixture was not distributed evenly between the solid particles, agglomerates of solid material (e.g., conductive additives) may remain. In some embodiments, such agglomerates may be smaller than visible to the naked eye, but these agglomerates may still cause the slurry to be "dry" or "brittle." Additionally, slurries with a small amount of mixing energy may not be ductile, which may include a tendency for the material to break rather than spread when formed.

[0060]

[0092] Increasing the mixing energy may improve the homogeneity of the mixture. Allowing mixing to continue may ultimately impart excessive mixing energy to the slurry. For example, as described herein, excessive mixing energy may produce a slurry characterized by low electrical conductivity. Adding mixing energy to the slurry may break down and disperse the conductive additive agglomerates, which may have a tendency to form a network-like conductive matrix, as described above with respect to Figures 3 and 4. As mixing continues, this network may break down as the carbon particles separate from one another, forming a more homogeneous carbon dispersion on a microscopic scale. Such overdispersion and loss of network may manifest as a loss of electronic conductivity, which is undesirable for an electrochemically active slurry. Additionally, slurries that have been given excessive mixing energy may exhibit unstable rheological properties. Because the carbon network affects the mechanical properties as well as the electronic properties of the slurry, compositions that are overmixed tend to appear "wetter" than slurries that have a lower amount of mixing energy. Slurries that experience excessive amounts of mixing energy also tend to have poor long-term compositional homogeneity, as the solid phase tends to settle due to gravity. Thus, a particular composition may have favorable electrical and / or rheological properties when mixed in the proper amounts. For any given formulation, there is an optimal range of mixing energies to provide acceptable dispersion, electrical conductivity, and rheological stability.

[0061]

[0093] 11-13 are plots showing, respectively, an exemplary blending curve, a comparative blending curve for low and high active material loadings for the same carbon additive loading, and a comparative blending curve for low and high carbon additive loadings for the same active material loading.

[0062]

[0094] FIG. 11 shows a mixing curve including specific mixing energy 1110, speed 1140, and torque 1170 of a slurry according to an embodiment. The first zone 1173 shows the addition of ingredients. In some embodiments, the active material is added to the mixer, followed by the electrolyte, and finally the conductive additive (carbon black). The carbon additive takes the longest to add to the mixing bowl due to the difficulty of incorporating the light, flyable powder into the relatively dry mix. The torque curve 1170 provides an indication of viscosity, specifically viscosity change. Adding carbon black increases the viscosity of the mix, thus increasing the torque required to mix the slurry. The increased viscosity indicates that a mechanical network of carbon is being formed. As mixing continues in the second zone 1177, the mixing curve shows the dispersion of ingredients and the relatively low viscosity, as evidenced by the decrease in the torque required to mix the slurry.

[0063]

[0095] Figure 12 shows the difference between low and high active material loadings. From this curve, it can be seen that the length of time required to add the conductive carbon additive is roughly equivalent for low and high active material loadings, but the overall torque (and therefore the mixing energy) is much higher at the higher active material loading, which indicates a much higher viscosity.

[0064]

[0096] FIG. 13 shows the difference between low and high loadings of conductive carbon additive for the same active material loading. The mixing curve for the high carbon loading includes specific mixing energy 1310, speed 1340, and torque 1373. The first zone 1373 shows the addition of the ingredients. The addition of carbon black increases the viscosity of the mixture, so the torque required to mix the slurry increases, as seen in the first mixing zone 1375. The increase in viscosity indicates that a carbon network is being formed. As mixing continues in the second zone 1377, the mixing curve shows the dispersion of the ingredients and a relatively low viscosity, as evidenced by the decrease in the torque required to mix the slurry. Note that the time required to add the carbon conductive additive is much longer for the high carbon loading, and the overall torque (and mixing energy) is also much higher. This mixing curve shows that the carbon loading has a much greater effect on the viscosity of the material than the active material loading.

[0065]

[0097] As described herein, the compositional homogeneity of a slurry generally improves with mixing time, and the compositional homogeneity can be characterized by a mixing index. FIG. 14 shows the specific energy input required to achieve different mixing indices for slurries with different conductive additive loadings. As shown, a larger specific energy input is required to achieve a desired specific index, for example, about 0.95, as the volume percent of conductive additive increases in the slurry formulation. In some embodiments, the slurry is mixed until it has a mixing index of about 0.8, about 0.9, about 0.95, or about 0.975, including all mixing indices in between.

[0066]

[0098] 15 illustrates the effect of mixing on certain slurry parameters, including the mixing index and electronic conductivity of the slurry, according to one embodiment. The mixing curve 1580 rises monotonically, while the electronic conductivity 1590 first increases (as the conductive network disperses in the medium), reaches a maximum, and then decreases (as the network breaks down due to "overmixing").

[0067]

[0099] In some embodiments, processing parameters can affect electronic conductivity, which is an important parameter for electrochemically active slurries. For example, FIG. 16 demonstrates that processing time can be selected to modify the electronic conductivity and morphology of a semi-solid electrode. An example of such a result is shown in FIG. 16, which shows the conductivity of a particular slurry containing about 35% NMC and about 2%-15% conductive additive C45 as a function of mixing time. As can be seen in FIG. 16, longer mixing times can result in samples with reduced conductivity.

[0068]

[0100] Similarly, Figures 17A-17D are micrographs of slurries subjected to two different mixing times, showing that aggregation of the carbon conductive additive tends to increase in sample 1710 mixed for a longer time (Figures 17A-17B) compared to sample 1720 mixed for a shorter time (Figures 17C-17D).

[0069]

[0101] In some embodiments, mixing time can simultaneously affect the mixing index and conductivity of an electrode slurry. FIG. 18 shows the effect of mixing time on the mixing index and conductivity of various slurry formulations containing about 45%-50% NMC and about 8% C45. In the measurements of mixing index presented herein and thereafter, a 0.12 mm sample was collected from a batch of electrode slurries having a total volume greater than the sum of the individual sample volumes. 3The mixing index is measured by removing a sample volume of 100 μm. Each sample volume of the slurry is heated in a thermogravimetric analyzer (TGA) with flowing oxygen gas according to a time-temperature profile starting with a 3 minute hold time at room temperature followed by heating at 20° C. / min to 850° C., and the cumulative weight loss between 150° C. and 600° C. is used to calculate the mixing index. As shown in FIG. 18, the mixing index is observed to increase, while the electrical conductivity is observed to decrease with increasing mixing time. In these embodiments, a good compromise between electrical conductivity and mixing index is observed at a mixing time of about 2 minutes, e.g., a slurry composition composed of 50% NMC and 8% C45 has been observed to have a mixing index of about 0.95 and an electrical conductivity of about 0.02 S / cm. Further mixing adversely affects the electrical conductivity.

[0070]

[0102] Figure 19 shows the effect of mixing time on the mixing index and conductivity of various slurry formulations containing about 45%-50% PGPT and about 2%-4% C45. For the 50% PGPT and 2% C45 mixture, the conductivity is observed to increase first, reach a peak at 4 minutes of mixing time, and then decrease by more than 2-fold at 24 minutes, which is consistent with the trend described in Figure 15. Thus, the mixing time required to obtain the optimum mixing index and conductivity of the slurry depends on the slurry formulation.

[0071]

[0103] In some embodiments, shear rate can affect mixing dynamics and conductivity. As a result, in some embodiments, selection of mixing element rotation speed, vessel and / or roller size, clearance dimensions / geometry, etc. can affect conductivity. FIG. 20 is a plot showing conductivity as a function of mixing time for two different shear conditions. As shown, the slurry that underwent lower shear mixing 2010 is less sensitive to overmixing. The slurry that underwent higher shear mixing 2020 has a slightly higher peak conductivity, requires less mixing to reach maximum conductivity, and is more sensitive to overmixing. In some embodiments, the optimal mixing time can be 20 seconds, 2 minutes, 4 minutes, or 8 minutes, including the mixing times in between.

[0072]

[0104] In some embodiments, the particle size, shape, aspect ratio, and distribution of the solid particles in the slurry suspension can be selected to determine the loading level.

[0073]

[0105] In some embodiments, temperature control during processing can be used, which can reduce electrolyte evaporation. Controlling the temperature of the slurry can improve the rheological, electrical conductivity, and / or other properties of the slurry.

[0074]

[0106] In some embodiments, the electrolyte can include a mixture of solvents with different levels of volatility and vapor pressure. Temperature can affect the evaporation rate of this mixture and also which components preferentially evaporate before other components, which can change the composition and / or performance of the electrolyte. Figure 21 shows the percentage loss of electrolyte with temperature and mixing duration. The overall reduction in electrolyte and loss of the more volatile components of the electrolyte in the slurry mixture can reduce the ionic conductivity of the slurry and subsequently increase the voltage polarization, reducing the efficiency and capacity of the battery. By reducing and / or controlling the processing temperature, the evaporation and subsequent changes in the composition of the slurry can be reduced, making it a more easily controllable process.

[0075]

[0107] In some embodiments, for example, if electrolyte loss occurs, a "compensation" step can be added to the process. This step can include adding excess electrolyte and / or electrolyte components (e.g., more volatile electrolyte components) at some stage of processing. This addition can be done during initial mixing of the electrolyte, during final cell assembly, or at any other stage.

[0076]

[0108] In some embodiments, temperature control can also be used to control the viscosity of the electrolyte, which can affect the rheological behavior of the slurry. FIG. 22 illustrates the effect of various temperatures on the apparent viscosity and apparent shear stress of an anode slurry composition including about 45% PGPT and about 4% C45, according to an embodiment. The anode slurry was formulated at a first temperature of −2° C. and a second temperature of 5° C. As the temperature of the slurry and / or electrolyte decreases, the viscosity increases. As the viscosity of the electrolyte increases, more force is exerted on the solid particles therein while the suspension flows. An electrolyte and / or slurry with increased viscosity tends to make the solid components of the slurry (active and conductive additives) move slower and less prone to accumulate and become a “plug” of solid material. FIG. 23 illustrates the effect of various temperatures on the apparent viscosity and apparent shear stress of a cathode slurry composition including about 50% NMC and about 8% C45, according to an embodiment. The cathode slurry was formulated at a first temperature of 5° C. and a second temperature of about room temperature (RT) (eg, 25° C.) Similar to the anode slurry formulation of FIG 22, the viscosity of the cathode slurry increases with decreasing temperature.

[0077]

[0109] In some embodiments, the temperature of the electrolyte and / or slurry can affect the adhesion of the slurry to other materials, such as process equipment. At lower temperatures, the slurry may exhibit reduced levels of adhesion to typical materials used in processing. Conversely, when applying the slurry to materials where adhesion is desired (e.g., metal foils or polymeric films), increasing the slurry / material interface temperature can act to promote adhesion.

[0078]

[0110] In some embodiments, the processing temperature can be about 10° C. In some embodiments, the processing temperature can be less than 10° C. The processing temperature can be selected to improve the flow stability of the slurry, for example, by adjusting the viscosity of the liquid phase (e.g., electrolyte). In other words, for a given flow geometry, slurry composition, and driving force, the slurry may experience loss of compositional uniformity (i.e., coalesce) at one temperature, but not at a different temperature. In some embodiments, the flow stability of the slurry can be adjusted (e.g., by selection of temperature) to improve the transport of the material through the process equipment (e.g., extruder, extrusion die, etc.). In some embodiments, the flow stability of the slurry can be adjusted to reduce adhesion of the slurry to the process equipment (e.g., calendar rolls, cutting blades, etc.). In some embodiments, the flow stability of the slurry can be adjusted to induce a desired adhesion to a laminate substrate (e.g., metal foil or polymer film). In some embodiments, the processing temperature can be adjusted to minimize or otherwise control the amount of electrolyte evaporation. In some embodiments, the processing temperature can be varied throughout the process to achieve desired properties at various steps.

[0079]

[0111] In some embodiments, ultrasonication can be used to modify the conductive network in the slurry. For example, vibratory excitation (sonication, vibration, acoustic) can be applied to the mixing device (in vessel or in situ), the conveying / blending device, and / or the slurry itself.

[0080]

[0112] In some embodiments, the conductive additive can have aggregation and cohesive properties (surface energy and interparticle forces) that can be adjusted during and / or after one or more process steps by other means, such as temperature, exposure to light or other controlled radiation, application of an electric or magnetic field, use of the additive in the liquid phase of the slurry, a dedicated coating on the active material, addition of chemical components to the conductive additive, and / or operation of an electrochemical operating configuration, etc. For example, salts can be added before, during, and / or after processing.

[0081]

[0113] The battery electrolyte can include one or more solvents, such as various organic carbonates. In some embodiments, the battery electrolyte can include one or more salts. In some embodiments, the electrolyte can contain other additives, such as surfactants, dispersants, thickeners, and / or any other suitable agents. In some embodiments, the additives can adjust the properties of the electrolyte, such as promoting flowability, processability, compositional stability, processability, and / or overall manufacturability. The additives can include fluorocarbonate derivatives, such as those developed by Daikin Industries. These additives can adjust the slurry properties in a desirable way, such as (1) increasing the viscosity of the liquid phase, which expands the range of shear rates that can be used for processing while maintaining compositional homogeneity between the fluid and solids, (2) improving lubricity - which expands the sliding area during flow, preserving homogeneity and potentially reducing the energy input associated with processing, and (3) reducing the vapor pressure of the mixture, reducing losses during processing, especially in unconfined spaces. In some embodiments, such additives can have a negative effect on electrochemical performance, but the benefits they bring to battery production can outweigh the negative effects.

[0082]

[0114] In some embodiments, the following battery configurations can utilize the methods described herein: (1) both electrodes are slurry-based, (2) one electrode is slurry-based and the other is conventionally cast, and (3) one electrode is slurry-based and the other is designed to consume and utilize a gas phase reactant, e.g., oxygen from air. Designs include a single anode-cathode pair (unit cell), prismatic assemblies with multiple anode / cathode pairs stacked on top of each other, spiral wound assemblies, jelly roll assemblies, and other variations.

[0083]

[0115] In some embodiments, the active material can include lithium titanate, graphite, silicon alloys, tin alloys, silicon-tin alloys, lithium iron phosphate, lithium transition metal oxides, magnesium compounds, bismuth, boron, gallium, indium, zinc, tin, antimony, aluminum, titanium oxide, molybdenum, germanium, manganese, niobium, vanadium, tantalum, iron, copper, gold, platinum, chromium, nickel, cobalt, zirconium, yttrium, molybdenum oxide, germanium oxide, or any other suitable active material. In some embodiments, the conductive additive can include carbon (high, e.g., Ketjen black or low, e.g., C45, specific surface area, graphite-natural or synthetic, graphene, nanotubes or other nanostructures, vapor grown carbon fiber, pelletized carbon, hard carbon, etc.), metal powders (e.g., aluminum, copper, nickel), carbides, and mixtures thereof. In some embodiments, the electrolyte included in the slurry can include ethylene carbonate, propylene carbonate, butylene carbonate, and carbonized or fluorinated derivatives thereof, and the family of acyclic dialkyl carbonate esters, such as dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, dibutyl carbonate, butyl methyl carbonate, butyl ethyl carbonate, butyl propyl carbonate, y-butyrolactone, dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, diethyl ether, sulfolane, methyl sulfolane, acetonitrile, propiononitrile, ethyl acetate, methyl propionate, ethyl propionate, dimethyl carbonate, tetraglyme, and the like.

[0084]

[0116] In some embodiments, the progression of the mixing index over time for a fixed RPM (e.g., 100 RPM) mixing speed may depend on the composition of the materials being mixed. For example, FIG. 24 shows the mixing index at 100 rpm over a period of time for a first anode composition comprising about 45% NMC and about 8% C45, and a second anode composition comprising about 50% NMC and about 8% C45. The mixing index in FIG. 25 shows the mixing index at 100 rpm over a period of time for a first anode composition comprising about 45% PGPT and about 4% C45, and a second anode composition comprising about 50% PGPT and 2% C45. In each case, nine samples having volumes ranging from about 0.1 to 0.2 cubic millimeters were used to determine the amount of mixing index. As shown in FIG. 24 and FIG. 25, the cathode and anode slurries show an increase in the mixing index with mixing time. As shown in FIG. 25, the mixing index plateaus after a certain mixing time, for example, 8 minutes, after which further mixing does not cause an increase in the mixing index.

[0085]

[0117] In some embodiments, different mixing processes may produce different degrees of mixing (i.e., mixing index) and conductivity for the same anode and / or cathode composition. For example, FIG. 26 shows the mixing index and conductivity for an anode composition including about 35% PGPT and about 2% C45 mixed for 4 minutes using four different mixing techniques (e.g., hand mix, roller, sigma, and CAM) at a fixed mixing speed of 100 RPM. As shown, the sigma achieves better uniformity (i.e., higher mixing index), but the roller achieves higher conductivity. Furthermore, under these mixing conditions, the CAM achieves the highest uniformity (e.g., mixing index of about 0.96) and conductivity (e.g., 0.33 S / cm). FIG. 27 shows the mixing index and conductivity for a first cathode composition including about 35% NMC and 8% C45, and a second electrode composition including about 45% NMC and 8% C45, both using two different mixing techniques (e.g., CAM and roller) at a fixed mixing speed of 100 RPM for 4 minutes. The 35% NMC / 8% C45 slurry achieves a higher mixing index in the roller mixer, whereas the 45% NMC / 8% C45 slurry achieves a higher mixing index in the CAM roller.

[0086]

[0118] In some embodiments, the type of mixing process used may also affect the conductivity of the slurry. For example, FIG. 28 shows the mixing index and conductivity of an anode composition containing about 45% PGPT and about 4% C45 mixed for a period of 1 minute or 4 minutes using a first mixing process (e.g., roller blade) or a second mixing process (e.g., CAM blade). As shown here, for a relatively short mixing time (e.g., 1 minute), some mixing types (e.g., roller) actually achieve higher uniformity than other mixing types (e.g., CAM). However, after a certain period of time (e.g., 4 minutes), the mixing index of the two mixing types is reversed, with CAM producing higher uniformity. Furthermore, in some cases, even higher conductivity can be achieved (e.g., 0.45 S / cm) after mixing for a longer period of time.

[0087]

[0119] In some embodiments, the mixing time can affect the flowability of the slurry, which is an indicator of the stability of the slurry. For example, Figures 29-30 show data from rheometer testing evaluating the compositional stability of a first anode slurry formulation containing about 45% PGPT and 4% C45, and a second anode slurry formulation containing 50% PGPT and about 2% C45, respectively. The first and second anode slurry formulations were mixed for 1 minute, 2 minutes, 4 minutes, or 8 minutes, respectively. At a stable set of process conditions, the pressure required to move the slurry usually remains relatively constant over time. The time scale of the pressure deviation from plateau is an indicator of stability. In Figure 30, the first anode slurry formulation with the highest stability is the formulation with the intermediate mixing time of 4 minutes, while slurries mixed for shorter (1 minute and 2 minutes) and longer (8 minutes) are less stable. A similar trend is observed for the second anode slurry formulation in Figure 30. 31 shows micrographs of the first and second anode slurries mixed for various periods of time as described herein, as shown, the first and second anode slurries mixed for 4 minutes are the most stable.

[0088]

[0120] Referring now to Figures 32-33, data are from rheometer testing evaluating the compositional stability of a first cathode slurry formulation containing about 50% NMC and 8% C45, and a second cathode slurry formulation containing 45% NMC and about 8% C45, respectively. The first and second cathode slurry formulations were mixed for 4 minutes or 8 minutes, respectively. Results for the slurries mixed for 1 minute are not shown because they were too unstable to hold their shape. As shown in Figures 30 and 31, the first and second cathode slurries mixed for 4 minutes or 8 minutes show equally good rheological properties. Figure 34 shows micrographs of the first and second cathode slurries mixed for various periods of time as described herein. As shown, the first and second cathode slurries mixed for 1 minute are unstable and break down, while the first and second cathode slurries mixed for 4 minutes or 8 minutes are stable.

[0089]

[0121] Like viscosity, conductivity, homogeneity, and rheological parameters are slurry properties that can be measured outside of the electrochemical cell. They are used as indicators of potential electrochemical performance, life, and processability, and are important "figures of merit" for slurries. That is, other parameters such as ionic conductivity, electrokinetic response such as impedance, elastic modulus, wettability, optical properties, and magnetic properties can be used as indicators of electrochemical performance.

[0090]

[0122] In some embodiments, determining whether a slurry has useful electrochemical properties may include verifying the performance of the slurry in an electrochemical cell. A discharge capacity at a current rate of C / 10 or greater that is at least 80% of the theoretical capacity of the electrode over a cell voltage range of 50% to 150% of the discharge voltage at which the magnitude of the differential capacity dQ / dV reaches a maximum value can serve as a criterion definition for a slurry to have useful electrochemical properties. The following examples illustrate the electrochemical properties of various semi-solid electrodes formed using the slurry preparation methods described herein. These examples are for illustrative purposes only and are not intended to limit the scope of the present disclosure.

[0091] Example 1

[0123] An LFP semi-solid cathode was prepared by mixing 45% by volume of LFP and 2% by volume of carbon black with an ethylene carbonate / dimethyl carbonate / LiPF6 based electrolyte. A batch mixer with a roller blade attachment was used to prepare the cathode slurry. Mixing was performed at 100 rpm for 2 minutes. The semi-solid slurry had a mixing index of greater than 0.9 and a solubility of 1.5×10 -4The slurry had a conductivity of 1000 S / cm. Electrodes 250 mm thick were made from the slurry and tested against a Li metal anode in a Swagelok cell configuration. The cells were tested using a Maccor battery tester and cycled between a voltage range of V=2-4.2V. The cells were charged using constant current-constant voltage, with constant current rates of C / 10 and C / 8 for the first two cycles, then C / 5 for the subsequent cycles. After constant current charging, the constant voltage is held at 4.2V until the charge current decreases below C / 20. The cells were discharged over a range of C rates between C / 10 and 5C.

[0092]

[0124] FIG. 35A shows the charge and discharge capacity as a function of discharge C-rate for the semi-solid electrode of Example 1, and FIG. 35B shows a representative charge and discharge curve at low C-rate. The nominal cell capacity of 2.23 mAh corresponds to the fully utilized LFP cathode active material. It can be seen that the majority of the cell capacity is obtained at the test conditions up to C-rate of 1C.

[0093] Example 2

[0125] An NMC semi-solid cathode was prepared by mixing 45% by volume of NMC and 8% by volume of carbon black with an ethylene carbonate / dimethyl carbonate / LiPF6 based electrolyte. The cathode slurry was prepared using a batch mixer with a roller mill blade attachment. The semi-solid slurry had a mixing index of greater than 0.9 and a solubility of 8.5×10 -3 Mixing was carried out at 100 rpm for 4 minutes to give a conductivity of 100 S / cm. The cathode was tested against a Li metal anode using the same cell configuration as in Example 1. The cell was tested using a Maccor battery tester and cycled between a voltage range of V=2-4.3V. The cell was charged using constant current-constant voltage, with constant current rates of C / 10 and C / 8 for the first two cycles, then C / 5 for the subsequent cycles. After constant current charging, the constant voltage was held at 4.2V until the charging current was below C / 20. The cell was discharged over a range of C rates between C / 10 and 5C.

[0094]

[0126] FIG. 36A shows the charge and discharge capacity as a function of discharge C-rate for the semi-solid electrode of Example 2, and FIG. 36B shows a representative charge and discharge curve at low C-rate. The nominal cell capacity of 3.17 mAh corresponds to full utilization of the NMC cathode active material over the voltage range tested. It can be seen that the majority of the cell capacity is obtained at the test conditions with a C-rate up to C / 2.

[0095] Example 3

[0127] An NMC semi-solid cathode was prepared by mixing 55% by volume of NMC and 4% by volume of carbon black with an ethylene carbonate / dimethyl carbonate / LiPF6-based electrolyte. A batch mixer with a roller blade attachment was used to prepare the cathode slurry. The semi-solid slurry had a mixing index of greater than 0.9 and a pH of 8.4×10 -4 Mixing was performed at 100 rpm for 4 minutes to give a conductivity of 1.5 S / cm. The cathode slurry was tested against Li metal using the same cell configuration and test procedure as in Example 2.

[0096]

[0128] FIG. 37A shows the charge and discharge capacity as a function of discharge C-rate for the semi-solid electrode of Example 3, and FIG. 37B shows a representative charge and discharge curve at low C-rate. The nominal cell capacity of 2.92 mAh corresponds to full utilization of the NMC cathode active material over the voltage range tested. It can be seen that the majority of the cell capacity is obtained at the test conditions with a C-rate up to C / 2.

[0097] Example 4

[0129] An NMC semi-solid cathode was prepared by mixing 60% by volume of NMC and 2% by volume of carbon black with an ethylene carbonate / dimethyl carbonate / LiPF6 based electrolyte. The cathode slurry was prepared using a batch mixer with a roller blade attachment. Mixing was performed at 100 rpm for 4 minutes. The cathode slurry was tested against Li metal using the same cell configuration and test procedure as in Example 2.

[0098]

[0130] FIG. 38A shows the charge and discharge capacity as a function of discharge C-rate for the semi-solid electrode of Example 4, and FIG. 38B shows a representative charge and discharge curve at low C-rate. The nominal cell capacity of 3.70 mAh corresponds to full utilization of the NMC cathode active material over the voltage range used. It can be seen that the majority of the cell capacity is obtained at the test conditions with a C-rate up to C / 2.

[0099]

[0131] In some embodiments, cell stability under cycling tests can also be used to evaluate the performance of the slurry and / or electrochemical cell. Stability means retaining a sufficiently high, e.g., 99% or more, electrochemical capacity between cycles. The following examples demonstrate cell stability under cycling tests for two slurry formulations prepared using the semi-solid electrode preparation methods described herein.

[0100] Example 5

[0132] An NMC semi-solid cathode was prepared by mixing 35% by volume of NMC and 8% by volume of carbon black with an ethylene carbonate / dimethyl carbonate / LiPF6 based electrolyte. A batch mixer with a roller blade attachment was used to prepare the cathode slurry. Mixing was performed at 100 rpm for 4 minutes. This resulted in a mixing index of 0.987 and a 5×10 -3 A semi-solid cathode suspension was produced with a conductivity of 0.19 S / cm. A graphite semi-solid anode was prepared by mixing 35% by volume graphite and 2% by volume carbon black in an electrolyte of the same composition as used for the cathode. The anode slurry formulation was mixed at 100 rpm for 20 seconds to produce a semi-solid anode suspension with a mixing index of 0.933 and a conductivity of 0.19 S / cm. Electrodes were formed from the cathode and anode semi-solid slurries, each with a thickness of 500 μm. The electrodes were used to produce a 20 cm2 electrode with a thickness of approximately 0.19 S / cm2 for both the cathode and anode. 2An NMC-graphite based electrochemical cell was formed with an active area of ​​1.0 μm. The cell was cycled between 2.75 and 4.2 V at various C rates. Over this voltage range, the expected specific capacity of the NMC cathode is 155 mAh / g. The cell was cycled using a constant current-constant voltage charge (CC-CV) and constant current discharge protocol between 2.75 and 4.2 V. At certain test stages, pulse charge and discharge tests were performed (indicated by "DCR" on the plot). During the DCR test cycles, the capacity value for that cycle appears close to zero on the plot (e.g., cycles 14, 34, and 55). In the constant current-constant voltage charge stage, the cell was subjected to a constant current at a prescribed rate, such as CC / 10, and when a voltage limit was reached, the cell was charged at a constant voltage until the current dropped below C / 20, after which it was switched to discharge. A constant current was used for all discharge stages. The discharge current was the same current as the charge current for that cycle. For example, a CC-CV / 10 cycle defined on the chart means that the cell is charged at a constant current of C / 10, followed by a constant voltage charge until the current drops to C / 20. The cell is then discharged at C / 10 until a voltage floor is reached. The number of cycles of that type of charge / discharge protocol is indicated as "x number of cycles." For example, "CC-CV / 5×3" means that during that test phase, the cell is charged at a constant current of C / 5, followed by a constant voltage hold of 4.2V, and the phase is repeated three times.

[0101]

[0133] FIG. 39A shows the results of charge / discharge cycling of the electrochemical cell of Example 5. The electrochemical cell exhibits a capacity corresponding to about 160 mAh per gram of NMC at the first charge / discharge cycle, and maintains a capacity of about 120 mAh / g of NMC after 100 charge / discharge cycles. FIG. 39B shows a representative charge and discharge curve of the electrochemical cell. The cell capacity measured for the electrochemical cell was 215 mAh.

[0102] Example 6

[0134] An NMC semi-solid cathode was prepared by mixing 45% by volume of NMC and 8% by volume of carbon black with an ethylene carbonate / dimethyl carbonate / LiPF6 based electrolyte. A batch mixer with a roller blade attachment was used to prepare the cathode slurry. Mixing was performed at 100 rpm for 4 minutes. This produced a semi-solid cathode suspension with a mixing index of 0.973 and a conductivity of 0.0084 S / cm. A graphite semi-solid anode was prepared by mixing 50% by volume of graphite and 2% by volume of carbon black in the same electrolyte as the cathode. The anode slurry formulation was mixed at 100 rpm for 20 seconds to produce a semi-solid anode suspension with a mixing index of 0.962 and a conductivity of 2 S / cm. The cathode and anode semi-solid slurries were used to form electrodes with a thickness of 500 μm each. The electrodes were used to form a semi-solid cathode and anode suspension with a thickness of approximately 20 cm. 2 An NMC-graphite based electrochemical cell was fabricated with an active area of ​​1.2 kV. The cell was cycled using a constant current-constant voltage charge (CC-CV) and constant current discharge protocol between 2.75 and 4.2 V, similar to that shown in Example 5. Over this voltage range, the expected specific capacity of the NMC cathode is 155 mAh / g.

[0103]

[0135] FIG. 40A shows the results of charge / discharge cycling of the electrochemical cell of Example 6. The electrochemical cell exhibits a capacity corresponding to about 170 mAh per gram of NMC at the first charge / discharge cycle, and maintains a capacity of about 100 mAh / g of NMC after 30 charge / discharge cycles. FIG. 40B shows a representative charge and discharge curve of the electrochemical cell. The cell capacity measured for the electrochemical cell was 305 mAh.

[0104]

[0136] While various embodiments of systems, methods and devices have been described above, it should be understood that they have been presented by way of example only and not limitation. While the methods and steps described above show certain events occurring in a particular order, those skilled in the art having the benefit of this disclosure will recognize that the order of certain steps may be changed and such changes are in accordance with variations of the invention. Also, certain steps may be performed simultaneously in parallel processes where possible and may also be performed sequentially as described above. While embodiments have been shown and described in detail, it will be understood that various changes may be made in form and detail.

Claims

1. 1. A method for preparing a semi-solid electrode, comprising the steps of: combining a quantity of an active material with a quantity of an electrolyte to form an intermediate material; combining a conductive additive with the intermediate material to form an electrode material; mixing the electrode materials to form a suspension having a mixing index of at least about 0.80; forming a semi-solid electrode from the electrode material; The method includes:

2. The method of claim 1 , wherein the electrode material becomes a stable suspension when formed into the semi-solid electrode.

3. The method of claim 1 , wherein the electrode material is mixed until the suspension has a mixing index of at least about 0.

90.

4. The method of claim 3 , wherein the electrode material is mixed until the suspension has a mixing index of at least about 0.

95.

5. The method of claim 4 , wherein the electrode material is mixed until the suspension has a mixing index of at least about 0.

975.

6. The electrode material is at least about 10 -6 10. The method of claim 1, further comprising mixing the electrode material until it has a conductivity of 100 S / cm.

7. The electrode material is at least about 10 -5 7. The method of claim 6, wherein the electrode material is mixed until it has a conductivity of 100 S / cm.

8. The electrode material is at least about 10 -4 8. The method of claim 7, wherein the electrode material is mixed until it has a conductivity of 100 S / cm.

9. The electrode material is at least about 10 -3 9. The method of claim 8, wherein the electrode material is mixed until it has a conductivity of 100 S / cm.

10. The electrode material is at least about 10 -2 10. The method of claim 9, wherein the electrode material is mixed until it has a conductivity of 100 S / cm.

11. The electrode material is -1 10. The method of claim 1, further comprising mixing the electrode material until it has an apparent viscosity of less than about 100,000 Pa-s at an apparent shear rate of 0.15 to 100.

12. The electrode is -1 12. The method of claim 11, wherein the electrode material is mixed until it has an apparent viscosity of less than about 10,000 Pa-s at an apparent shear rate of 1000 .mu.m.

13. The suspension is stirred for 1,000 s -1 13. The method of claim 12, wherein the suspension is mixed until it has an apparent viscosity of less than about 1,000 Pa-s at an apparent shear rate of 1000 rpm.

14. The method of claim 1 , wherein the amount of the active material is from about 20% to about 75% of the electrode material by volume.

15. The method of claim 14, wherein the amount of the active material is from about 40% to about 75% of the electrode material by volume.

16. The method of claim 15, wherein the amount of active material is about 60% to about 75% of the electrode material by volume.

17. The method of claim 1 , wherein the amount of the electrolyte is from about 25% to about 70% by volume of the electrode material.

18. The method of claim 17, wherein the amount of the electrolyte is about 30% to about 50% by volume of the electrode material.

19. 20. The method of claim 18, wherein the amount of the electrolyte is about 20% to about 40% by volume of the electrode material.

20. The method of claim 1 , wherein the amount of the conductive material is from about 0.5% to about 25% of the electrode material by volume.

21. The method of claim 20, wherein the amount of conductive material is from about 1% to about 6% of the electrode material by volume.

22. 10. The method of claim 1, wherein the mixing index is evaluated at a sample volume that is the cube of the thickness of the formed semi-solid electrode ±10%.

23. 0.12mm 3 2. The method of claim 1, wherein the mixing index is evaluated at a sample volume of ±10%.

24. 1. A method for preparing a semi-solid electrode, comprising the steps of: combining a quantity of an active material with a quantity of an electrolyte to form an intermediate material; combining a conductive additive with the intermediate material to form an electrode material; A blending index of at least about 0.80 and a blending index of at least about 10 -6 mixing the electrode materials to form a stable suspension having an electronic conductivity of 100 S / cm; The method includes:

25. 25. The method of claim 24, wherein the amount of the active material is from about 20% to about 75% by volume of the stable suspension, the amount of the conductive additive is from about 0.5% to about 25% by volume of the stable suspension, and the amount of the electrolyte is from about 25% to about 70% by volume of the stable suspension.

26. 25. The method of claim 24, wherein the mixing is performed in a high shear mixer.

27. 25. The method of claim 24, wherein the mixing is performed in a centrifugal planetary mixer.

28. 25. The method of claim 24, wherein the mixing is performed in a planetary mixer.

29. The method of claim 24, wherein the mixing is performed in a sigma mixer.

30. The method of claim 24, wherein the mixing is performed in a CAM mixer.

31. 25. The method of claim 24, wherein the mixing is performed in a roller mixer.

32. 25. The method of claim 24, wherein the mixing provides a specific mixing energy to the electrode material of at least about 90 J / g.

33. 33. The method of claim 32, wherein the mixing provides a specific mixing energy to the electrode material of at least about 100 J / g.

34. 26. The method of claim 25, wherein the mixing provides a specific mixing energy to the electrode material of about 90 J / g to about 150 J / g.

35. 34. The method of claim 33, wherein the mixing provides a specific mixing energy to the electrode material of about 100 J / g to about 120 J / g.

36. A semi-solid electrode comprising: about 20% to about 75% by volume of active material; about 0.5% to about 25% by volume of a conductive material; about 25% to about 70% by volume of an electrolyte; A semi-solid electrode that is a suspension having a mixing index of at least about 0.

80.

37. 37. The semi-solid electrode of claim 36, wherein the suspension has a mixing index of at least about 0.

90.

38. 40. The semi-solid electrode of claim 37, wherein the suspension has a mixing index of at least about 0.

95.

39. 40. The semi-solid electrode of claim 38, wherein the suspension has a mixing index of at least about 0.

975.

40. The semi-solid electrode has a thickness of at least about 10 -6 37. The semi-solid electrode of claim 36 having an electronic conductivity of 1.0 S / cm.

41. The semi-solid electrode has a thickness of at least about 10 -5 41. The semi-solid electrode of claim 40 having an electronic conductivity of 1.0 S / cm.

42. The semi-solid electrode has a thickness of at least about 10 -4 42. The semi-solid electrode of claim 41 having an electronic conductivity of 1.0 S / cm.

43. The semi-solid electrode has a thickness of at least about 10 -3 43. The semi-solid electrode of claim 42 having an electronic conductivity of 1.0 S / cm.

44. The semi-solid electrode has a thickness of at least about 10 -2 44. The semi-solid electrode of claim 43 having an electronic conductivity of 1.0 S / cm.

45. The semi-solid electrode is -1 37. The semi-solid electrode of claim 36, having an apparent viscosity of less than about 100,000 Pa-s at an apparent shear rate of .

46. The semi-solid electrode is -1 46. ​​The semi-solid electrode of claim 45, having an apparent viscosity of less than about 10,000 Pa-s at an apparent shear rate of .

47. The semi-solid electrode is -1 47. The semi-solid electrode of claim 46, having an apparent viscosity of less than about 1,000 Pa-s at an apparent shear rate of

48. 37. The method of claim 36, wherein the mixing index is evaluated at a sample volume that is the cube of the thickness of the formed semi-solid electrode ±10%.

49. 0.12mm 3 37. The method of claim 36, wherein the mixing index is evaluated at a sample volume of ±10%.

Citation Information

Patent Citations

  • Method of manufacturing positive electrode for lithium-ion secondary battery, method of manufacturing lithium-ion secondary battery, positive electrode for lithium-ion secondary battery, and lithium-ion secondary battery

    JP2010157361A

  • Method and apparatus for manufacturing electrode for electrochemical element, and electrochemical element

    JP2011076824A

  • High energy density redox flow meter

    JP2011524074A